Formation conditions and enrichment mechanisms of the Jurassic lacustrine organic-rich shale in the East Fukang Sag, Junggar Basin, NW China: A reassessment based on organic geochemistry - Qiao, Jinqi; Luo, Qingyong; Zhang, Ye; Wang, Dandan; Cui, Hao; Shang, Xiaoqing; Liu, Luofu; Zhang, Tong (Frontiers in Earth Science, 2023)
Chemical composition of sediments is often used to evaluate the paleoclimate condition, provenance, tectonic setting, organic matter (OM) depositional condition, and paleoproductivity. However, the validity of these proxies has long been questioned. The comprehensive use of organic and inorganic multi-indicators in combination when interpreting issues related to terrestrial shales should be advocated. The paleodepositional environment, origin of OM and factor controlling OM accumulation in the Early Jurassic Badaowan (J1b) and Sangonghe (J1s) as well as Middle Xishanyao (J2x) lacustrine shales in the East Fukang Sag are reassessed by using the geochemical characteristics of the OM. Some previous knowledge is updated, and some knowledge is further supported by more evidence. The typical clay-rich shale developed under a lacustrine sedimental environment, and the thermal maturity of these organic-rich shales has entered the oil window and formed economic hydrocarbon potential for the tight-oil and shale-oil reservoirs. The paleoclimate conditions of the study area were warm and humid from the early to middle Jurassic periods but were colder and drier after the middle Jurassic. The salinity of the water column ranged from freshwater to middle-brackish conditions. The J2x formation was deposited under oxic conditions, while J1b and J1s formations developed under suboxic and reducing environmental conditions. The J2x Formation OM mainly derived from higher plants was deposited in a terrestrial environment, while the OM of J1b and J1s formations was a mixed OM derived from higher plants and bacteria with little algae deposited under bay/estuary environments alternated with terrestrial environments. It is effective to reflect the paleoclimate by element index and judge the salinity by the updated element thresholds, but it is not effective to evaluate the paleoredox conditions by common elemental ratios and to evaluate paleoproductivity by Ba in the study area.